2019
DOI: 10.1186/s11689-019-9267-z
|View full text |Cite
|
Sign up to set email alerts
|

In the line-up: deleted genes associated with DiGeorge/22q11.2 deletion syndrome: are they all suspects?

Abstract: Background 22q11.2 deletion syndrome (22q11DS), a copy number variation (CNV) disorder, occurs in approximately 1:4000 live births due to a heterozygous microdeletion at position 11.2 (proximal) on the q arm of human chromosome 22 (hChr22) (McDonald-McGinn and Sullivan, Medicine 90:1-18, 2011). This disorder was known as DiGeorge syndrome, Velo-cardio-facial syndrome (VCFS) or conotruncal anomaly face syndrome (CTAF) based upon diagnostic cardiovascular, pharyngeal, and craniofacial anomalies (McD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 419 publications
(442 reference statements)
2
76
0
Order By: Relevance
“…These phenotypes, like several others associated with heterozygous deletion of 22q11.2 genes (reviewed by 1 , 54 ), are subtle and variable. This partial penetrance may reflect stochastic variation in gene expression associated with aneuploidy ( 55 , 56 ), including in the LgDel +/− CNgV ( 7 ).…”
Section: Discussionmentioning
confidence: 77%
“…These phenotypes, like several others associated with heterozygous deletion of 22q11.2 genes (reviewed by 1 , 54 ), are subtle and variable. This partial penetrance may reflect stochastic variation in gene expression associated with aneuploidy ( 55 , 56 ), including in the LgDel +/− CNgV ( 7 ).…”
Section: Discussionmentioning
confidence: 77%
“…Claudin-5, expressed in brain endothelial cells, forms a major component of the BBB barrier-forming tight junctions ( Morita et al, 1999 ; Greene et al, 2019 ). Claudin-5 maps to a region on chromosome 22 where small deletions cause the 22q11 deletion syndrome, which is found in 30% of SCZ cases ( Murphy, 2002 ; Motahari et al, 2019 ). People with this syndrome are haploinsufficient for claudin-5 and have increased odds of developing SCZ ( Fiksinski et al, 2018 ; Greene et al, 2018 ).…”
Section: How the Peripheral Immune System Gains Access To The Cns In mentioning
confidence: 99%
“…To date, the reasons for this clinical heterogeneity remain unclear and could encompass a complex combination of both gene x gene (GxG) and gene x environment (GxE) interactions. Some studies have recently shown evidence that GxG interactions modulate risk for schizophrenia in 22q11DS (6)(7)(8). In particular, Cleynen et al (6) observed that the presence of common genetic variants outside of the 22q11.2 locus and known to be associated with risk for schizophrenia-also known as the polygenic risk score for schizophrenia-is more frequent in individuals with 22q11DS diagnosed with a psychotic disorder compared to those without psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the reasons for this clinical heterogeneity remain unclear and could encompass a complex combination of both gene x gene (GxG) and gene x environment (GxE) interactions. Some studies have recently shown evidence that GxG interactions modulate risk for schizophrenia in 22q11DS ( 6 8 ). In particular, Cleynen et al.…”
Section: Introductionmentioning
confidence: 99%